The use of nutritional supplements by elite Portuguese swimmers - Teixeira, V. H.; Sousa, M.; Moreira, P. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
A well-planned diet provides the athlete with adequate levels of nutrients; however, there are many sportsmen/sportswomen taking nutritional supplements (NSs) in spite of their possible contamination with prohibited compounds and the unproved efficacy of the majority of them. In Portugal, no official data regarding the consumption of NSs is available. This study aimed to determine the prevalence and determinants of the use of NSs by elite Portuguese swimmers. Methods Thirty six swimmers (14 women; 17.3 years), belonging to the Portuguese national team, volunteered to participate in this study. Between January and March, subjects were asked to complete a questionnaire that included questions to characterise the use of NSs, and a semiquantitative food-frequency questionnaire. Results The prevalence of the use of NSs was 91.7%, with a mean consumption of 3.7 NSs per swimmer (between 1 and 10). Regarding the type of supplements and fluids ingested, the most used were sport drinks (75.8%), magnesium (60.6%), multivitamins/minerals (57.6%), proteins (27.3%) and vitamin C (21.2%), with no significant gender and age category (<18 years vs. =18 years) differences. The most frequent reasons for the intake of NSs were: `to improve sports performance` (57.6%), `to have more energy/to reduce fatigue` (57.6%), `to accelerate recovery` (42.4%), "to have more focus" (15.2%, with an age-based difference: <18 years=23.6%; =18 years=64.3%; p=0.034) and "to prevent/to treat diseases or injuries" (15.2%). Physicians (57.6%), coaches (30.3%), family (24.2%) and the swimmer him/herself (21.1%) were the main source of information and advice, with no statistical differences between gender and age groups. The estimated intakes for most nutrients (16 studied) were above the recommendations. For girls between 19 and 30 years (n=4), the estimate mean ingestion of potassium (4305 mg/day), calcium (938 mg/day), folate (385 mcg/day), vitamin D (3.6 mcg/day) and vitamin E (10.8 mg/day) was under the recommendations. For boys with 14-18 years (n=11), the estimate mean intake of potassium (4392 mg/day), vitamin D (4.8 mcg/day) and vitamin E (13.2 mg/day) was under the recommendations. For males with ages between 19 and 30 years (n=11), only the estimated mean intake of vitamin E (12.9 mg/day) was under the recommendations. Conclusions The prevalence of the consumption of NSs was high and not justified due to an adequate nutrient intake by swimmers. In general, the type of NSs used and their determinants were not associated with gender or age group. Therefore, dietary education could be beneficial to maximize elite swimmers` performance and health benefits that result from optimal nutrition.